An Endoplasmic Reticulum Specific Pro‐amplifier of Reactive Oxygen Species in Cancer Cells. (8th April 2021) - Xu, Hong‐Gui; Schikora, Margot; Sisa, Miroslav; Daum, Steffen; Klemt, Insa; Janko, Christina; Alexiou, Christoph; Bila, Galyna; Bilyy, Rostyslav; Gong, Wenjie; Schmitt, Michael; Sellner, Leopold; et al.
Abstract: The folding and export of proteins and hydrolysis of unfolded proteins are disbalanced in the endoplasmic reticulum (ER) of cancer cells, leading to so‐called ER stress. Agents further augmenting this effect are used as anticancer drugs including clinically approved proteasome inhibitors bortezomib and carfilzomib. However, these drugs can affect normal cells, which also rely strongly on ER functions, leading, for example, to accumulation of reactive oxygen species (ROS). To address this problem, we have developed ER‐targeted prodrugs activated only in cancer cells in the presence of elevated ROS amounts. These compounds are conjugates of cholic acid with N‐alkylaminoferrocene‐based prodrugs. We confirmed their accumulation in the ER of cancer cells, their anticancer efficacy, and cancer cell specificity. These prodrugs induce ER stress, attenuate mitochondrial membrane potential, and generate mitochondrial ROS leading to cell death via necrosis. We also demonstrated that the new prodrugs are activated in vivo in Nemeth‐Kellner lymphoma (NK/Ly) murine model. Abstract : A fluorogenic N‐alkylaminoferrocene‐based prodrug activated by reactive oxygen species in vitro and in vivo was developed that is cancer cell specific and targets the endoplasmic reticulum.